Groundwater management in land administration: a spatio-temporal perspective - Ghawana, Tarun (2012)
Although the use of land and water is intertwined, specifics for groundwater management are not effectively dealt with in the laws and other institutional mechanisms related to land. Provisions for groundwater aspects in land management are there, but with a focus on the land itself. Land rights and restrictions are more or less static, lacking enough flexibility to incorporate the relatively short interval spatio-temporal dynamics of groundwater resources in the land management and regulation mechanisms. This leads to a gap between the scientific inputs and policy-decision making. The paper suggests the adaptation of a spatial information science based approach to bridge the gap between the technical and administrative aspects of groundwater management. The land administration domain model (LADM) provides a basic set of elements capable of supporting the inclusion of basic groundwater modeling elements into land administration, making it possible to create a support system for the management of land and water. For this purpose, spatial and temporal dimensions under the legal-administrative and spatial unit components of the standard LADM model are reviewed. The paper shows that the advancement of spatial technologies is capable of providing solutions for global issues such as groundwater resource management. As a first step towards implementation of these technologies, it is essential to include spatio-temporal dynamics properly in the standard data models. Increased knowledge of the behaviour of groundwater resources, supported by a technical system built on a land administration counterpart, could help improve greater sustainability in the use of such resources. Considering the specific arrangements of rights, parties and spatial units this could, if desired, also provide the base for a regulated private market in groundwater assets. Further research will be needed to fully operationalize and implement such data models, which ultimately could produce outputs at case study level which can help to formulate policies regarding natural resources more on the basis of technical inputs.